Treatment of autoimmune thrombocytopenia in a case of chronic hepatitis C with ursodeoxycholic acid - Naz, Hasan; Aslan, Vahap (The Journal of Infection in Developing Countries, 2009)
Pegylated interferon (PEG-IFN) alpha and ribavirin therapy has become the standard treatment in chronic hepatitis C virus (HCH)-infected patients. While thrombocytopenia associated with IFN use is frequently observed among these patients, autoimmune thrombocytopenia is one of the rarely observed adverse effects. In the present report, we present a case with chronic HCV infection in which autoimmune thrombocytopenia developed at week 7 of PEG-IFN alpha 2b plus ribavirin therapy. The patient subsequently received ursodeoxycholic acid (UDCA) treatment. Although there is not an adequate number of studies on this subject, it was concluded that the use of UDCA in cases of autoimmune thrombocytopenia that have developed due to PEG-IFN treatment in chronic HCV infection is a favorable option.